Patterns of dental problems and time gap in utilization of dental services by patients visiting a dental college in North Kerala - Kuldeep Singh Shekhawat; Praveen Dinatius; T Vanishree; C B Thasneem (Wolters Kluwer Medknow Publications, 2019)
Introduction: Access to dental services is generally regarded as a necessary condition for achieving population-level oral health and well-being. Oral diseases are largely preventable by regular home oral care and preventive dental visits which help in the early detection and treatment of oral diseases. Aim: The objective was to assess the patterns of dental problems and time gap in utilizing dental services. Materials and Methods: A retrospective study was conducted on outpatients who visited Century Dental College, Kasaragod, Kerala, for duration of 6 months from July 2017 to December 2017. The data were collected from medical records from the outpatient department. Descriptive statistics were used to analyze the data. Results: A total of 2593 cases were analyzed. The mean age was 35.66 ± 13.2 years. The most common dental problem reported was decayed teeth (29.3%) followed by dental pain (23.5%) and deposits on teeth (14.4%). Only 3.98% of the patients visited immediately the next day as soon as they noticed black discoloration and/or informed about their decayed tooth. Males reportedly approached the college more than females for most of the chief complaints except for replacement of missing teeth. Conclusions: The most common dental problem reported was decayed teeth followed by dental pain and deposits on teeth. Only 3.77% of the patients reported for a routine dental checkup. Twelve percent of patients reported immediately the next day after experiencing dental pain. Most of the participants visit a dentist only if they had a problem.